Geometrical Evaluation of an Overtopping Wave Energy Converter Device Subject to Realistic Irregular Waves and Representative Regular Waves of the Sea State That Occurred in Rio Grande—RS - Paiva, Maycon da Silveira; Mocellin, Ana Paula Giussani; Oleinik, Phelype Haron; dos Santos, Elizaldo Domingues; Rocha, Luiz Alberto Oliveira; Isoldi, Liércio André; Machado, Bianca Neves (Processes, 2025)
Among the various potential renewable energy sources, sea waves offer significant potential, which can be harnessed using wave energy converter (WEC) devices such as overtopping converters. These devices operate by directing incident waves up a ramp into a reservoir. The water then passes through a turbine coupled with an electrical generator before returning to the ocean. Thus, the present study deals with the geometrical evaluation of an overtopping WEC, where the influence of the ratio between the height and length of the device ramp (H1/L1) on the amount of water mass (M) that enters the reservoir was investigated. Numerical simulations were performed using ANSYS-Fluent software, 22 R1 version, to generate and propagate realistic irregular (RI) waves and representative regular (RR) waves found in the coastal region of the municipality of Rio Grande, in the state of Rio Grande do Sul, southern Brazil. Consequently, through constructal design, the optimal WEC geometry for both wave approaches were identified as the same, where (H1/L1)o=0.30. Thus, considering the RI waves, M= 200,820.77 kg was obtained, while, considering the RR waves, M= 144,054.72 kg was obtained.